Assessing the Pedestrianizing Process in Streets - Elmira Nasri (صفه)
Closing streets to vehicular traffic and converting then to walkways,i.e. the pedestrianizing process, has become a fashionable trend inmany Iranian cities—irrespective of how successful this experience hasbeen. There is no consensus however, on how such streets should beselected or what are the outcomes expected. This paper tries to developa hierarchical analytic framework for assessing walkways, reduce theirnegative impacts and improve their quality. To this end, a qualitativeresearch methodology is employed based on evidence. The requireddata was collected through a study of technical texts, semi-structuredinterviews with 5 specialists, and interviews with some 30 residents,storekeepers and users in 3 walkways in Tehran. A content analysis ofthis data demonstrates that certain factors have a strategic priority overintrinsic criteria, such as economic and administrative aspects and userbenefits. The intrinsic criteria which are prioritized include: the potentialto attract pedestrians, the potential for provision of mixed functions, andthe feasibility of closing the street to vehicular traffic.